Involvement of Farm Women in Decision making Regarding Dairy Farming in Junagadh District of Gujarat State - Patel, S. J.; Kumar, R.; Patel, A. S.; Patel, N. R.; Parmar, V. N. (Indian Journal of Hill Farming, 2017)
India is an agriculture based country and livestock sector is an integral component. Women play crucial and significant role in livestock rearing, all spheres of economic life and contribute richly towards national income. A survey study was conducted to acquire the first hand information on Personal and socio-economic characteristics and Decision making of farm women regarding dairy farming and also correlation between these two variables studied in Junagadh district of Gujarat state, India. A simple random sampling technique was used in the selection of dairy farm women. The total sample constitutes 200 dairy farm women, four talukas and five village from each taluka. Total ten (10) respondents selected from each village of the district. The data were collected by personal interview technique through a structural schedule. In Personal and socio-economic characteristics, majority (73.50 %) of the farm women belonged to middle age group, 31 per cent of the farm women were educated up to primary level of education. Majority (44 %) of the dairy farm women were from SEBC caste category, majority (72 %) of the farm women belonged to low level of income (